A Novel Mutation c.3392G>T of COL2A1 Causes Spondyloepiphyseal Dysplasia Congenital by Affecting Pre-mRNA Splicing - Fan, Lihong; Ji, Longfei; Xu, Yuqing; Shen, Guosong; Tang, Kefeng; Li, Zhi; Ye, Sisi; Shen, Xueping (Frontiers in Genetics, 2022)
Spondyloepiphyseal dysplasia congenital (SEDC) is a rare chondrodysplasia caused by dominant pathogenic variants in COL2A1. Here, we detected a novel variant c.3392G > T (NM_001844.4) of COL2A1 in a Chinese family with SEDC by targeted next-generation sequencing. To confirm the pathogenicity of the variant, we generated an appropriate minigene construct based on HeLa and HEK293T cell lines. Splicing assay indicated that the mutated minigene led to aberrant splicing of COL2A1 pre-mRNA and produced an alternatively spliced transcript with a skipping of partial exon 48, which generated a predicted in-frame deletion of 15 amino acids (p. Gly1131_Pro1145del) in the COL2A1 protein. Due to the pathogenicity of the variation, we performed prenatal diagnosis on the proband’s wife, which indicated that the fetus carried the same mutation.